Linear Programming Approach for Optimal Profit Mix of Cassava Grates and Flour - Loreño, Dustin; Cirenuela, Junmarie; Cagabhion, Harold; Jurial, Mitchelyn; Apas, Genalyn; Remoto, Elma; Fuentes, Carla Jean; Casas, Marie Cris; Falcone, Quenne; Gonzaga, Luzviminda; Dawal, Annabeth; Cuesta, Mary Joy; Flores, Paulo; Ortiz, Jessica (Frontier Management Science, 2024)
The research aimed to identify the optimal combination of cassava grates and flour to maximize the profit of a project initiated by the Philippine Root Crops Research and Training Center at Visayas State University. The findings revealed that the most profitable combination consisted of 125 kg of cassava grates and 25 kg of flour, resulting in an optimum profit of Php 4,250.00 for the entire production. The study highlighted that the project was constrained by limited inputs, preventing it from exceeding the optimal quantities of the two products. To enhance the profitability of both products, adjustments in the resources utilized during production were necessary. While the current production of cassava grates falls below the optimum quantity, indicating room for increased production with the existing inputs, the production of cassava flour had already reached its optimal level. To achieve optimal quantity and profit, the project must implement strategies to prevent resource wastage.